Identifying Barriers to Optimal Pain Management in ICU Nurses: A Cross-Sectional Analysis - Iklima, Nurul; Maidartati, Maidartati; Irawan, Erna; Nurlianawati, Lia; Nuryanti, Lisna (Journal Medical Informatics Technology, 2025)
Pain is a sensitive indicator in the nursing process, so assessment and pain management are the key factors to determining the quality of care and patient satisfaction, especially in critical care areas. The poor handling of pain can have a negative impact on critical patients. Pain management is influenced by internal factors and external factors. Internal factors are knowledge and attitudes while external factors are factors of organizational support and professional authority. This study aims to analyze the factors associated with the implementation of pain management. This study is a quantitative study with an analytic correlation design. The total sample of 84 nurses was taken using the total sampling technique. Data were collected using five questionnaires, namely Regarding Pain Knowledge and Attitudes Survey questionnaire, Perceived Organizational Support, Nursing Autonomy, and Current Practice Related to Pain Assessment and Pain Management. The results showed that the implementation of pain management was quite optimal (51.2%), factors related to the value (p <0.005), The dominant factors contribution score (35.7% for knowledge). The implementation of pain management is quite optimal, but there are some obstacles related to the implementation of pain management including knowledge, attitudes, and professional authority. Nurses are expected to increase their knowledge and competence through education and training to maintain the quality of the implementation of pain management.